Frequency of biochemical abnormality in elderly with fracture neck of femur (Tikrit Journal of Pharmaceutical Sciences, 2023)
To assess the frequency of abnormal results of bone profile tests including serum calcium, phosphate, alkaline phosphatase and the results of parathyroid hormone in patients with fracture neck of femur. The study includes a group of 100 elderly patients ages 60 years and older with fracture neck of femur, and 100 healthy elderly persons without fracture neck of femur from the same age range, served as a control group .The subjects selected for the study were free from secondary risk of metabolic bone disease apart from age, genetic and menopause. Individual of both groups were referred to the laboratory of Department of Biochemistry/ College of Medicine/ University of Mosul. The study was conducted during the period from 17th February 2008 up to 22nd of December 2008. Measurements of serum parathyroid hormone was conducted by Enzyme-Linked ImmunoSorbent Assay, and serum calcium; phosphate, albumin, total alkaline phosphatase activity was conducted by colorimetric method. A high frequency of combined abnormal biochemical tests 79% among the fractured group was found, compared to 46% in non fractured, which is highly significant (p˂0.001). Combined abnormal biochemical tests (osteomalacia) in elderly person may contribute to risk of fracture